PENGARUH KADAR AIR TERHADAP KUAT GESER PADA TANAH LANAU - Endaryanta, Endaryanta (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Landslide disaster such as bank slide or embankment slide often occurs. This it begins with a simple problem, that is infiltration of rain water into soil causing the decrease of soil strength resulting in collapse. The research tries to explain the water influe'nce at the shear strength of soil to find out how much water content may induce soil collapse. This experimental research was conducted in the soH laboratory using mud from Imogiri, Bantul conditioned in several water contents (from 10% to 500/0) and direct shear tests were then applied. This experiment would produce CD (internal soil shear angle), c (soil cohesion), and finally slide off soil safety factor (F). This research has resulted: 1. at a low water content (10% ) the CD soil is low, the CD increases by increasing the water content, but the next increas of water' content causes a decrease of CD. The maximum CD (32.5°) reaches at 23% of water content. 2. at a low water content (10%) the c soil is low, the c increases by increasing the water content, but the next increasing of water content causes a decrease of c. The maximum c (0.076 kg/cm2 ) reaches at 22% of water content. 3. at a low water content (100/0) the F soil is low, the CD increases by increasing the water content, but the next increasing of water content causes a decrease of F. The maximum F reaches at 21% of water content. Key words: mud, soil, water content, shear strength, cohesion, land slide.